Code-Switching Identification Amongst Adult Spanish Learners in Online English Language Class - Maulana, Dimas; Alfinda, Rio (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores code-switching among adult Spanish-speaking learners in an online ESL setting. Through qualitative observation and discourse analysis, eight functions were identified: specific topic of conversation, clarification and repetition, communicative efficiency, translation strategy, participation encouragement, identity expression, interjection, and quotation. Learners used Spanish to express culturally embedded ideas and resolve lexical gaps, while teachers facilitated understanding through targeted translation. References to Papá Noel and Reyes Magos highlight how switching reflects cultural pride and supports meaning-making. Findings suggest that code-switching enhances learner engagement, affirms identity, and fosters pedagogical clarity, making it a powerful tool in bilingual instruction.